Research on mobile edge computing and caching in massive wireless communication network - Yongming HUANG; Chong ZHENG; Zhengming ZHANG; Xiaohu YOU (Tongxin xuebao)
For the large-scale network mobile edge computing and caching technology of future 6G mobile communications, firstly, the architectures and principles of mobile edge computing and caching in large-scale wireless networks were introduced, and the necessity and universality were clarified.Then, from the perspective of the five key issues in the mobile edge computing and caching enabled large-scale wireless network, including computing offloading, edge caching, multi-dimensional resource allocation, user association and privacy protection, the recent researches and further pointed out the future development trends and research directions were reviewed and analyzed.Finally, for the privacy preservation issue, a federated learning based privacy-preserving scheme was proposed.Simulation results show that the proposed scheme can simultaneously preserve user privacy and improve the quality of service.